Technical-tactical, physiological and neuromuscular effects of opponent number in simulated judo combats: a pilot study - Boscolo del Vecchio, F.; Silveira Coswig, V.; Bartel Farias, C.; Dimare, M.; Miarka, B. (Journal of Physical Education and Sport, 2018)
Present investigation compared technical/tactical actions, physiological and neuromuscular responses in simulated judo combats with and without opponent changes. Six judokas (22.5±3.0 years-old) participated of three pilot experimental sessions with simulated combats, each one with a different number of opponents (1x1; 1x2; 1x5) in a randomized order. Subjects performed a warm-up and a five-minute combat per session, which was realized in accordance with international rules, with exception for Ippon interruption. Experimental sessions were compared by repeated measures analysis of variance followed by Bonferroni post-hoc, p<0.05. There was a time effect to HR (p=0.001), RPE (p=0.001) and LAC (p=0.001), where the values of intra and post-Randori were higher than pre-Randori. In addition, for LAC and RPE, the values of the post-Randori were higher than the pre and intra-Randori, which emphasizes an increasing linear trend for both variables. A time effect was observed, resulting in a 16 to 11% performance loss in handgrip strength for the non-dominant hand (p=0.027), 36% of loss in time for the isometric test on the bar in the 1x1 situation, and 31% of loss for the 1 x 5 situation, between pre- and post-Randori moments (p=0.002). Upper limbs power, inferred by CMJ, showed a 5% performance loss for 1x1 and 1x2 situation and no loss for 1x5, with no differences between effort moments. Lower limbs power showed a 4%, 15%, and 13% decrease in the 1x1, 1x2, and 1x5 situations. Regarding technical-tactical analysis, the time effect was observed only for the 1x1 group, in which there was a greater volume of attempts in the 4th minute compared to the 1st minute (p=0.009). Kachinuki does not create additional stress for most variables compared to the traditional situation with only one opponent.